Ultisols & oxisols: enhancing their productivity for oil palm, rubber and cocoa cultivation - Ishak, Che Fauziah; Ismail, Roslan; Jusop, Shamshuddin; Wan Daud, Wan Noordin (Universiti Putra Malaysia Press, 2018)
The growth of the economy of the countries in emerging market in the tropics depends so much on agricultural crops, such as oil palm, rubber and cocoa. For the past many decades Malaysia has been leading in the R&D of these three most important plantation crops. However, books written on soil/agronomic practices leading to sustainable production of the crops are only a few. The objectives of writing this book are, therefore, to narrow the gap in knowledge between researchers and growers about the production of the commodities on sustainable basis and to alleviate the dearth of information on the arts and sciences of their productivity. The innovations that have been put in place to sustain crop production are explained in detail in this book. We hope that this book will be useful to students and researchers alike, especially those in the tropics.